Effect of Materialism on Pro-environmental Behavior Among Youth in China: The Role of Nature Connectedness - Wang, Jing; Huo, Yongquan (Frontiers in Psychology, 2022)
We designed three studies to to explore the effect of materialistic values on pro-environmental behavior among youth and the mediated role of nature connectedness between materialistic values and pro-environmental behavior. Through a self-report questionnaire survey (Study 1) and an experimental manipulation of materialistic values (Study 2), we found that materialistic values negatively predicted pro-environmental behavior, and that nature connectedness played a mediating role. Further, we used natural contact strategies to control the level of nature connectedness, and found that the negative impact of high materialistic values on pro-environment behavior decreased with the increase of nature connectedness, further supporting the mediating role of nature connectedness (Study 3). These results may contribute to the design of strategies that effectively mitigate the negative effects of materialistic values on pro-environmental behavior.